Business Transformation in the Era of Industry 4.0 In the Age of Technological Change - Joanna A. DYCZKOWSKA; Marcin OLKIEWICZ And Adam CZARNOTA (Communications of International Proceedings, 2025)
The object of transformation can be people, seen as individuals or as groups, as well as the organisations they create, in particular enterprises. The aim of this article is to introduce the idea of enterprise transformation in the period of Industry 4.0, which is the basis of the changes taking place in the enterprise, and then to identify the first changes of the transformation process in the organisation. The research problem formulated: what actions should an enterprise take in the period of Industry 4.0 in order to reach the level of a successful organisation and competitive advantage? It was shown that there is a significant research gap in this area regarding the company's digital technology implementation activities. The research method adopted is the analysis and criticism of the literature and observation of the transformation process in Polish enterprises. In the final conclusion, it was determined that the transformation of enterprises in the period of Industry 4.0 is subject to the implementation of digital technologies, this mainly concerns key issues for the modern socio-economic system, is currently one of the main areas of development of modern economic entities, which are enterprises. To carry out the digital transformation, Poland plans to allocate a total budget (excluding private investment) estimated at EUR 12.4 billion (1.6 per cent of GDP).
Keywords: transformation; AI; Industry 4.0; digital technology; processes